Pengaruh Karakteristik Perusahaan Terhadap Keputusan Penerapan Assurance Laporan Keberlanjutan (Studi Empiris pada Perusahaan yang Menerbitkan Laporan Keberlanjutan dan Terdaftar di Bursa Efek Indonesia Tahun 2012 – 2014) - Arif Rakhman (UNSIKA (Universitas Singaperbangsa Karawang), 2017)
This research aims to analyze the influence of firm characteristics to the decision of engagement sustainability reporting assurance (SRA) with using sample listing firms in Indonesia Stock Exchange between 2012 – 2014. Independent variable are size, profitability, and leverage. Dependent variable is sustainability report assurance and control variable in this research is type of industry. Data in this research obtained from national center for sustainability report, Indonesia Stock Exchange’s website (IDX), and firm’s website. Multivariate analysis is used to analyze factors influence the engagement decision of sustainability report assurance. Hypothesis testing uses logistic regression model with software IBM SPSS 22. The result shows that size, profitability, and leverage are not determinant factors sustainability report assurance. Whereas there is negative influence between controls variable type of industry to sustainability report assurance. The implication of this research are this research contributes to development of accounting literature specifically about sustainability report assurance in Indonesia.